Scolytinae y Platypodinae (Coleoptera: Curculiondae) de Tabasco, México - Falcón-Brindis, Armando; Pérez-de la Cruz, Manuel; Mata-Zayas, Ena Edith; de la Cruz-Pérez, Aracely; Sánchez-Soto, Saúl; Burelo-Ramos, Carlos M. (Instituto de Ecología, A.C., 2018)
The aim of the present study was to evaluate the diversity of Scolytinae and Platypodinae in five localities of Tabasco between December 2012 and April 2013. Ten flight intercept traps were used with ethyl alcohol as an attractant to collect insects in each site. A total of 4,232 specimens were collected from 62 species, of which 57 belong to Scolytinae and five to Platypodinae. The greatest diversity of species was obtained in Malpasito (MP) with a value of H´=2.11 and the lowest in Boca del Cerro (BC) with a value of H´=0.78, the highest species richness was recorded MP with 39 and the highest species abundance Francisco Rueda (FR) with 1,500 specimens. The genera Hypothenemus and Xyleborus presented the highest species richness with 10 and 7 respectively. The species Premnobius cavipennis Eichhoff, Xyleborus volvulus (Fabricius), Sampsonius dampfi Schedl, Hypothenemus interstitialis (Hopkins) and Corthylus papulans Eichhoff showed the highest abundance with 2,962 specimens, representing 69.99% of the total. The especies Cnesinus elegans Blandford, C. gracilis Blandford, Corthylocurus barbatus (Blandford), Chramesus crenatus Wood, H. effeminatus Wood, H. inaequalis Wood, H. columbi Hopkins and M. robustum (Schedl) are new records for Tabasco. The list of species of these insects in Tabasco, México continues to grow as new samples are taken, suggesting that it has not been possible to collect the real diversity supported by the ecosystems of the state.